(untitled) (Comparative Professional Pedagogy, 2023)
The article analyzes the experience of the leading European countries in implementing the concept of Education for Sustainable development (ESD). Official documents, which are the foundation of ESD policy, are studied and the works of leading scientists and pedagogues related to the issue are characterized. ESD provides learners with appropriate and up to date information on how to organize their life in a way that is friendly to environment and other people. It requires universities to shift education and professional training of students from a knowledge- to a more competence-based approach in their national curricula. This approach encourages the development of students’ sustainability competences. It also enables them to implement sustainability values, and embrace complex skills necessary to take or request action that restores and maintains eco-system health, enhances justice and generates visions for sustainable future. The core document used in higher education system of European countries to develop students’ ESD competences is “GreenComp – The European sustainability competence framework” which includes 4 competence areas and 12 competences that together make up a pillar for sustainability practice. ESD requires universities to promote transformative changes in learning in 4 different ways: 1) pluralizing limited agendas; 2) empowering collective influence; 3) politicizing power relations; 4) embedding learning systems. It is stressed that universities must implement ESD based on connectivism principle. Specific examples of this principle in action are described in the article. They include Urban Living Labs, which are a kind of collaboration aimed at implementing joint projects in the field of urban development and infrastructure improvement, and Academic Consultancy Training for master degree students in which they cooperate with students of other educational programs (specialties) and stakeholders to conduct interdisciplinary research and learning. To outline the ways European experience can be used in developing countries, namely Ukraine, legislative documents of the country related to ESD were characterized and the corresponding activities of Ukrainian universities (on the example of Khmelnytskyi National University) were described. In the result, a set of recommendations was prepared on how to improve the policy of ESD in developing countries using European experience.